Psychological distance: a qualitative study of screening barriers among first-degree relatives of colorectal cancer patients - Xueying Zhang; Yiheng Zhang; Jingyu Chen; Meifen Zhang; Ni Gong (BMC, 2021)
Abstract Background Colorectal cancer screening can reduce the incidence and mortality through early detection. First-degree relatives (FDRs) of patients with colorectal cancer are at high risk for colorectal cancer and therefore require colonoscopy. However, despite the high risk, screening adherence among FDRs remains low and the barriers to undergoing screening among FDRs in China are not clear. We explored the reasons why FDRs refused screening. Methods In this qualitative study, 28 semistructured, in-depth interviews were conducted face-to-face. Participants were recruited at two hospitals (an urban tertiary hospital and a community health center) in Guangzhou, South China. We used qualitative content analysis to analyze transcripts based on audio recordings and identify major themes and subthemes. Results Three major themes emerged related to FDRs' low screening participation. First, the emotional distance between FDRs and medicine was pulled away by uncomfortable feelings approaching hospitals and misunderstanding of cancer. Second, they confirmed their health state and minimized cancer risk if they had no signs in routine health examination, no symptoms and maintained a healthy, happy life. Third, they considered screening far from their daily life from the perspective of spatial distance and priority. Therefore, screening was not necessary in their view. Conclusions Healthcare professionals should narrow psychological distance between people and screening when promoting screening technology.